Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1029/2008gl033390
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of impacts from rising temperature on inflows to the Murray‐Darling Basin

Abstract: The 2001–2007 Australian drought was the hottest on record with inflows to Australia's longest river system, the Murray‐Darling, reaching an historical low. Here we examine the relative importance of rising temperature and decreasing rainfall over its catchment, the Murray Darling Basin (MDB). Although annual‐total inflow is more sensitive to rainfall over the southern MDB, where rainfall since 2001, has been the lowest on record, this alone can not explain the observed inflow decline. A relationship exists be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
200
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(208 citation statements)
references
References 9 publications
7
200
1
Order By: Relevance
“…This period is characterized by severe drought conditions, with the largest negative PDSI value of the 20th Century, close to À4 (Figure 1d). These low-rainfall years are exacerbated by anomalously warm temperatures of 0.3-0.6°C above the long-term average (Figure 1c) [Cai and Cowan, 2008a], contributing to the severity of the drought via increased potential evaporation [Nicholls, 2004].…”
Section: Resultsmentioning
confidence: 99%
“…This period is characterized by severe drought conditions, with the largest negative PDSI value of the 20th Century, close to À4 (Figure 1d). These low-rainfall years are exacerbated by anomalously warm temperatures of 0.3-0.6°C above the long-term average (Figure 1c) [Cai and Cowan, 2008a], contributing to the severity of the drought via increased potential evaporation [Nicholls, 2004].…”
Section: Resultsmentioning
confidence: 99%
“…[Cai and Cowan, 2008] have argued that runoff decline in SEA is related not only to declining rainfall but also to increasing temperature that presumably increases evaporation. However, [Donohue et al, 2010] showed that, despite increasing air temperatures, changes in vapour pressure, net radiation and wind speed result in declining PE for much of Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Increased evapotranspiration as a result of increased air temperatures, more interception structures and land use have dramatically reduced runoff (van Dijk et al 2006;Timbal and Jones 2008;MDBA 2009a). In the MDB, a 15% reduction of inflows has been observed for a 18C rise in average temperature; a 28C temperature rise by 2060 could result in a 55% reduction in inflows from reduced precipitation and increased evapotranspiration (Cai and Cowan 2008).…”
Section: Hydrology and Climate Changementioning
confidence: 99%